Perbedaan Sumpek Antara Wanita dan Pria Penghuni Pemukiman Padat di Kota Yogyakarta - Indra Wahyudi; Riang Gumanti (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2014)
This aim of this research was to understand the difference of sumpek between women and men who live in high density area in Yogyakarta, The women ability that is more adaptive on several aspects made the reasearcherformmulateda hypothesis